1987
DOI: 10.1111/j.1746-1561.1987.tb03214.x
|View full text |Cite
|
Sign up to set email alerts
|

School Nurses' Perceptions of Childhood Obesity

Abstract: A random sample of 250 nurses from the American School Health Association membership were sent a questionnaire concerning childhood obesity; 88% responded. Most (85%) believed normal weight was important to children's health and that school nurses should be role models by maintaining normal weight (77%). Most also believed counseling children and their parents about weight loss was difficult (71%) and that schools need to do more to alleviate childhood obesity (65%). At least 75% believed all schools should of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 23 publications
9
35
1
1
Order By: Relevance
“…Because school nurses provide most school health services (AAP, 2001), it seems likely that nurses will assume responsibility for oversight of obesity prevention services. Consistent with earlier studies assessing school nurse opinion about school-based obesity prevention (Price et al, 1987;Stang et al, 1997), this study found school nurses support the use of SHS for obesity prevention. Furthermore, nursing support for obesity prevention, as well as the likelihood of performing more child-and school-level obesity prevention tasks increased as perceived support from health care providers and school staff increased, suggesting that development and implementation of school-based obesity programs will benefit from a community-guided process, inclusive of school staff, health care providers, parents and students.…”
Section: Discussionsupporting
confidence: 79%
“…Because school nurses provide most school health services (AAP, 2001), it seems likely that nurses will assume responsibility for oversight of obesity prevention services. Consistent with earlier studies assessing school nurse opinion about school-based obesity prevention (Price et al, 1987;Stang et al, 1997), this study found school nurses support the use of SHS for obesity prevention. Furthermore, nursing support for obesity prevention, as well as the likelihood of performing more child-and school-level obesity prevention tasks increased as perceived support from health care providers and school staff increased, suggesting that development and implementation of school-based obesity programs will benefit from a community-guided process, inclusive of school staff, health care providers, parents and students.…”
Section: Discussionsupporting
confidence: 79%
“…To date, studies have relied on selfreport methods to assess bias and have often focused on schoolbased implementation of obesity prevention programs rather than on addressing specific attitudes or bias (Price, Desmond, & Ruppert, 1990;Price, Desmond, Ruppert, & Stelzer, 1987). It is also possible that negative beliefs on the part of educators could result from accurate impressions of overweight students they have encountered.…”
Section: Educatorsmentioning
confidence: 99%
“…More specifically, qualitative and quantitative findings indicate that the web-based features of the program are effective in providing school nurses with tools and resources to execute their role. School nurses are increasingly looked to as key players in the fight against childhood obesity but many require additional knowledge, support, and professional development to do this effectively (Hendershot et al 2008;Moyers et al 2005;Nauta et al 2009;Price et al 1987). Relative to the school nurses' role, the alignment with state reporting requirements, overall efficiency, and comprehensive nature of Health eTools for Schools are areas of particular strength.…”
Section: Discussionmentioning
confidence: 97%